The effect of psychological capital and job satisfaction toward millennials front line staff / Muhammad Akmal Hakim Rosli - Rosli, Muhammad Akmal Hakim (Faculty of Business and Management, 2018)
The purpose of this study is to examine the significant relationship between psychological capital and job satisfaction of millennials front line staff. The author propose that psychological capital has an effect toward job satisfaction on millennials front line staff. A theoretical model which psychological capital as independent variable and job satisfaction as dependent variable. This model is tested using data gathered from 100 front line staff. The results show resilience is the only dimension in psychological capital that have a significant relationship on job satisfaction toward millennials front line staff.